Creating a foundation for interactive heads-up displays - Astorsson, Billy; van Sommeren, Paul (My University, 2019)
Abstract Level 2 automation has been shown to lower the cognitive workload needed to operate vehicles. As a result, drivers may experience a cognitive underload while driving. This may incentivize the driver to use their phone, resulting in unsafe situations. This thesis lays a foundation for creating interactive heads-up displays (HUD) that may replace the need for using a phone. The focus is put on the user experience of the HUD specifically implemented in cars and trucks. In order to do so, several aspects within the scope of this research are investigated. User research, through cultural probes and context mapping, explores current use of phones. The results show the need for staying connected, and the development potential of an interactive HUD. A previously untested method, called the Blur method, is shown to be a better representation of HUD use than the industry-standard Occlusion method. It is further shown to be a valuable method for qualitatively evaluating interface designs. The look-down angle from the driver’s line of sight is shown to be essential in task performance, with an optimal angle being between 2.5° and 5° below the line of sight. A human-machine interface concept with level 2 Wizard-of-Oz automation is created based on the research in this thesis. The concept shows significantly positive results (p<0.05, n=12) on the attractiveness, perspicuity, efficiency, and simulation scales of the User Experience Questionnaire. This thesis presents 32 guidelines in the categories of HUD content, HUD interface, physical implementation and relations to the phone. The guidelines serve as a basis for designing a HUD that combines a safe, efficient interaction with an enjoyable user experience. The guidelines create a foundation for designing interactive HUDs, and the authors recommend a holistic approach into further research and development of the interactive HUD and potential guidelines.
Keywords: interactive heads-up display; level 2 automation; cognitive underload; blur method; look-down angle; user experience